ECONOMIC VALIDATION OF EFFICIENT MODEL FOR FINANCING OF CURRENT CAPITAL AT UKRAINIAN INDUSTRIAL ENTERPRISES - Mann, Ruslan (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2018)
The article analyzes the main strategies of formation and using of enterprises’ current assets. The types of current assets management policy of industrial enterprises in Ukraine are grounded. The actual type of the policy of current assets management at Ukrainian industry in 2015 is determined.